In Vitro Polyoma DNA Synthesis: Studies on an Early Temperature-Sensitive Mutant - Francke, Bertold (1974)
The polyoma ts-a function was investigated by using an in vitro DNA-synthesizing system. A comparison of systems derived from ts25 (a ts-a group mutant)-and ts1260 (a late group mutant)-infected cells showed that the activation energies for DNA chain elongation and the mechanisms of discontinous growth were identical for both mutants.